2012
DOI: 10.4172/2157-7110.1000184
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Modified Atmosphere Packaging and Calcium Chloride Dripping on the Quality and Shelf Life of Kurdistan Strawberries

Abstract: The present research was conducted to evaluate the effects of MAP and calcium chloride on some quality parameters of strawberry fruits stored at 4°C. Several quality parameters were monitored during the storage period. The samples were analyzed 0, 7, 14, 21 and 28 days during storage. Fruit weight, sugar content, chromatic parameters L*, a*, b*, fruit firmness, total titratable acidity, pH, sensory evaluation are analyzed. The results evidenced that the immersion of fruit in 0.5% calcium chloride solution (CaC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 41 publications
0
13
0
Order By: Relevance
“…It might be due to the reason that calcium gluconate make a film on surface and, thus, act as a barrier to water loss as well as the presence of glucose [32]. Since high respiration results in loss of sugars which is an important factor in perishability of strawberry fruits [2], the presence of glucose in calcium gluconate may contribute toward delaying senescence [1]. Thus, calcium gluconate was more effective than other calcium sources under study [36].…”
Section: Marketable Fruits (%)mentioning
confidence: 95%
See 2 more Smart Citations
“…It might be due to the reason that calcium gluconate make a film on surface and, thus, act as a barrier to water loss as well as the presence of glucose [32]. Since high respiration results in loss of sugars which is an important factor in perishability of strawberry fruits [2], the presence of glucose in calcium gluconate may contribute toward delaying senescence [1]. Thus, calcium gluconate was more effective than other calcium sources under study [36].…”
Section: Marketable Fruits (%)mentioning
confidence: 95%
“…The maximum mean weight loss observed in control (0% calcium) declined with increase of calcium concentration to the minimum with 1.5% calcium concentration. The interaction of calcium sources and concentrations revealed that application of calcium from different sources decreased the weight loss, and the maximum decrease in weight loss was recorded with calcium gluconate [20] at concentration of 1.5% probably due to delaying enzymatic activities responsible for moisture loss and senescence [1]. The superior performance of calcium gluconate in decreasing weight loss can be attributed to its hydrophobic nature, which improves the water vapor barrier by providing hydrophobicity to the surface [32].…”
Section: Influence Of Calcium Sources and Concentration On The Storagmentioning
confidence: 99%
See 1 more Smart Citation
“…SO 2 pads did not have a significant effect on tiratable acidity of strawberries and its content decreased continuously till end of storage (Jouki and Khazaei, 2012;Samiullah et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…The fruits treated with sulphur dioxide pad with various grams of KMS + citric acid had not recorded significant scores compared against initial score of 94 points (Table 5) (Pelayo et al, 2003). This might be due to high respiration and transpiration rates, high temperature, increased microbial infection, induce catabolic activity of strawberry fruits and had not control of loss of weight (Shin et al, 2008;Jouki and Khazaei, 2012;Srivastava and kumar, 2012).…”
Section: Resultsmentioning
confidence: 99%